Performance of Workability and Compressive Strength on Self-Compacting Geopolymer Concrete Based On High-Calcium Fly Ash With Addictive Admixture - Yuyun Tajunnisa; Nur Achmad Husin; Sigit Darmawan; Ridho Bayuaji; Raden Buyung Darmawan; Arwinda Aribah Cahyani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Geopolymer concrete has been developed as a replacement for conventional concrete with other pozzolan materials, which have a high silicate alumina content. Fly ash is a material that contains a high silicate alumina of 22%. The high content of Al and Si increases the compressive strength of concrete. High-calcium fly ash is abundantly found in Indonesia. However, it has not been widely used for industry or research, and this is due to the fast hardening time of concrete. Therefore, it has the potential to be developed. High-quality concrete has a low cement water factor that causes low workability in concrete. Self-compacting geopolymer concrete (SCGC) has been developed as a high-quality concrete innovation with high workability. Concrete is produced by using gravel, sand, fly ash, alkaline activator, and water materials. This study used 14 Molar levels of NaOH. The variations used were 0%, 3%, 5%, and 7% superplasticizers (SP) made from polycarboxylate. This study used a dry mixing method to overcome the setting time on concrete. The results show that the workability that can be achieved is 645mm, and the compressive strength achieved is 41.7 Mpa